Text Messages to Promote Secondary Prevention after Acute Coronary Syndrome (IMPACS trial) - Passaglia,Luiz Guilherme (2022)
Abstract Background Short message service (SMS) to promote healthcare improves the control of cardiovascular risk factors, but there is a lack of evidence in low and middle-income countries, particularly after acute coronary syndromes (ACS). Objective This study aims to evaluate whether the use of SMS increases risk factor control after hospital discharge for ACS. Methods IMPACS is a 2-arm randomized trial with 180 patients hospitalized due to ACS at a tertiary hospital in Brazil. Eligible patients were randomized (1:1) to an SMS intervention (G1) or standard care (G2) upon hospital discharge. The primary endpoint was set to achieve 4 or 5 points in a risk factor control score, consisting of a cluster of 5 modifiable risk factors: LDL-C <70mg/dL, blood pressure (BP) <140/90mmHg, regular exercise (≥5 days/week, 30 minutes/session), nonsmoker status, and body mass index (BMI) <25 kg/m2] at 6 months. Secondary outcomes were components of the primary outcome plus rehospitalization, cardiovascular death, and death from any cause. Results are designated as significant if p<0.05. Results From randomized patients, 147 were included in the final analysis. Mean age was 58 (51–64) years, 74% males. The primary outcome was achieved by 12 (16.2%) patients in G1 and 15 (20.8%) in G2 (OR=0.73, 95%CI 0.32–1.70, p=0.47). Secondary outcomes were also similar: LDL-C<70 mg/dl (p=0.33), BP<140/90 mmHg (p=0.32), non-smoker (p=0.74), regular exercise (p=0.97), BMI (p=0.71), and rehospitalization (p=0.06). Death from any cause occurred in three participants (2%), including one cardiovascular death in each group. Conclusion SMS intervention did not significantly improve cardiovascular risk factor control when compared to standard care in patients discharged after ACS in Brazil.